Why is it so difficult to understand why we don’t understand human systemic lupus erythematosus? Contemplating facts, conflicts, and impact of “the causality cascade paradigm” - Rekvig, Ole Petter (Frontiers in Immunology, 2025)
In attempts to understand systemic lupus erythematosus (SLE), we find ourselves in the intellectual cross-point between nosology, pathogenicity-oriented science, philosophy, empiricism, and qualified conjectures. A vital consequence in science theory is that scientific hypotheses that are not critically investigated are in danger of being transformed into scientific dogmas1. This statement has consequences for this study. Two central problematic aspects are discussed. For the first, we have to consider new selection principles for classification criteria—implying integration of the causality principle. Second, central historical data must be implemented if we aim to understand SLE. These data comprise famous descriptions of distinct, dynamically changing DNA structures linked to the genetic machinery. These unique structures have since their discoveries decades ago mostly been ignored in SLE research. Likewise, inconclusive dogmatic data indicate that different glomerular ligands are recognized by nephritogenic anti-dsDNA antibodies—exposed chromatin fragments or inherent membrane ligands. These incongruent models have not been comparatively and systematically investigated. Three research areas will be critically discussed: (i) selection and role of SLE classification criteria, a process that must imply the causality principle; (ii) definition and impact of anti-dsDNA structure-specific antibodies; (iii) incongruent pathogenic models that account for lupus nephritis. A precise and critically important question is if SLE itself is a response to a dominant unified cause that initiates a cascade of downstream effects (criteria) or if SLE represents combined responses to a random interplay of multiple cause-effect events. These principally different explanations are formally not excluded or accepted today. Currently, SLE may be regarded as a disease with phenotypic diversity, independently segregated manifestations with unresolved etiologies that are not unique to a single SLE phenotype. The focus for the present discussion is basically how we, by critical hypotheses, can re-consider science-based selection of SLE classification criteria in order to delimitate and rationalize SLE. Classification criteria, autoimmunity, DNA structures, and anti-dsDNA antibodies are integrated aspects in this discussion.